Effect of Microbial Phytase in Soybean Meal Based Broiler Diets Containing Low Phosphorous - Mondal, M.K.; Panda, S.; Biswas, P. (International Journal of Poultry Science, 2007)
A six wk feeding experiment was conducted with d-old four hundred broiler chicks (Ven Cobb) to determine the effects of microbial phytase (Allzyme) supplementation in soybean meal based broiler diet containing low phosphorous. These birds were randomly divided into four dietary treatment groups of 100 broilers each. Each treatment group was further sub-divided into five replicates of 25 broilers per replicate. The treatments groups were control; low phosphorus; low phosphorus plus 250 PU phytase/kg diet; low phosphorus plus 500 PU phytase/kg diet. There were significant effects of dietary treatments on body weight, body weight gain, feed intake and feed conversion ratio at 0 to 42 days. The body weight and the body weight gain of the broilers fed the control and low phosphorus plus phytase diet were heavier (p